Film characteristics of atmospheric pressure plasma-treated chitosan solution - Siao, Vera Angela (Archīum Ateneo, 2025)
Chitosan (Cs) is a biopolymer that can be used to create films with high swelling capacity. Its application, however, is restricted by its weak mechanical strength. To address this limitation, atmospheric pressure plasma (APP) treatment was integrated into the Cs film synthesis. This was done by exposing the Cs solution to air plasma at varying times—2, 4, and 6 min. Improved dissolution of Cs was observed in the scanning electron microscope images where no traces of excess Cs particles were found on the surface. Spectroscopic techniques such as optical emission spectroscopy, Fourier transform infrared spectroscopy, and Raman spectroscopy suggested that chain scission and cross-linking synergistically occurred to establish the network of the Cs films. This possible reaction mechanism of film formation was manifested as changes in the peak intensities of the different Cs attributes such as the pyranose ring, -OH, the C-O-C glycosidic, and the amide linkages. Shorter treatment time (2 min) resulted in the dominance of degradation where scission occurred to open the Cs rings. When using a longer treatment time (>4 min), cross-linking reactions occurred along the scission sites, which acted as initiation points. As a result, the hydrophilicity and swelling behavior of the Cs films were influenced by the APP treatment. The fabricated Cs films were generally hydrophilic. However, utilizing a longer treatment time decreased the hydrophilic nature of the film. A decreased swelling capacity for APP-treated Cs films also accompanied the decreased hydrophilicity. This observed phenomenon was attributed to the addition of Cs chains possibly caused by cross-linking. The study revealed that the water absorption ability of the Cs films was based on the relaxation of the Cs chains upon interaction with water. The integration of APP treatment for film synthesis may provide easier processing of Cs films.